Major unconformities/termination of extension events and associated surfaces in the South China Seas: Review and implications for tectonic development - Morley C. (2017)
© 2016 Elsevier Ltd. The distribution of unconformities and end of Cenozoic rifting events in the South China Seas (SCS) reflects both the modes of rift development, and the effects of driving mechanisms. Continental rifting began in the eastern basins during the Paleocene, and propagated westwards to the Vietnam basin margin in the Late Eocene. Continental breakup around 32-28 Ma caused a regional reduction or cessation in extensional activity, particularly affecting basins furthest from the spreading centre. Basins in the slope and deepwater area north of the spreading centre exhibit reduced fault activity until 21-20 Ma. Propagation of oceanic crust westwards between ~25 and 23 Ma, and termination of seafloor spreading sometime between 20.5 and 16 Ma affected fault activity in the Qiongdongnan, and Nam Con Song basins. In the Phu Khanh Basin and South, in the Dangerous Grounds area, extension continued until about 16 Ma, ending at the Red Unconformity. The end of seafloor spreading around 20.5 Ma reflects loss of extensional driving force as thinned continental crust entered the NW Borneo subduction zone. Controversially, a key component of the driving force maybe attributed to slab-pull. A transitional period of about 5-7 my between the onset of subduction of continental crust, and final jamming of the subduction zone (Deep Regional Unconformity, DRU) is inferred. The last pulse of extension was focussed in the western SCS, and terminated around 10.5 Ma. Detailed understanding of proto South China Seas development remains uncertain and controversial.